Aspects of ecologistic risk management in the warehouse of finished goods in the FMCG industry - Kulińska, Ewa; Giera, Julia (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Modern warehouse management can’t be based solely on the protection of stored products. It must be also enriched with elements protecting the natural environment. The aim of the article is the environmental aspect of risk management in the logistics process of storing finished products from the Fast Moving Consumer Goods industry. The research identified specific risk factors for the warehouse process. Methods of preventing the occurrence of a given risk factor have been indicated, while protecting the natural environment. The research methodology used in the article is ICOM cubes. Using this method, the risks that may occur in the warehouse process were identified and all elements influencing the given process are indicated. The implementation of changes in the operation of the warehouse process will significantly affect the natural environment and bring many benefits to warehouse companies, including financial and resource savings.